2001
DOI: 10.1088/0953-8984/13/18/302
|View full text |Cite
|
Sign up to set email alerts
|

Detection of efficient carrier capture in ultrathin InAs/GaAs layers using a degenerate pump-probe technique

Abstract: By analysing the carrier dynamics based on the rate equations and the change of the refractive index due to the efficient carrier capture, we have calculated the carrier capture process in the InAs/GaAs system detected by a simple degenerate pump-probe technique. The calculated results are found to be in good agreement with the experimental findings. Our results indicate that this simple technique, with the clear advantage of being easy to carry out, can be very useful in studying the carrier dynamics for some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…[ 38 ] Liu et al also reported a similar delayed rise of transient reflectivity in ultrathin InAs/GaAs layers. [ 39 ] The delayed peak was attributed to the carrier capture in ultrathin InAs layers which occurred over a few ps time scale. In another work, Wei‐liang et al had also reported a delayed rise of transient reflectivity signal in GaAs/AlGaAs MQW structure.…”
Section: Resultsmentioning
confidence: 99%
“…[ 38 ] Liu et al also reported a similar delayed rise of transient reflectivity in ultrathin InAs/GaAs layers. [ 39 ] The delayed peak was attributed to the carrier capture in ultrathin InAs layers which occurred over a few ps time scale. In another work, Wei‐liang et al had also reported a delayed rise of transient reflectivity signal in GaAs/AlGaAs MQW structure.…”
Section: Resultsmentioning
confidence: 99%
“…The probe light monitored only the time evolution of the electron spin in the InGaAs QW. A model based on the rate equations [29] and the Bloch-Torrey equations [5] is proposed to describe the spin transfer processes quantitatively. For the spin-polarized electrons which were generated in the GaAs layer and took part in the spin transfer processes, the time evolution of the spin magnetization can be expressed in the following equations:…”
Section: Resultsmentioning
confidence: 99%
“…With such a system, we studied electron spin transfer processes between two semiconductors of different gaps in an InGaAs/GaAs quantum well (QW) sample. The spin transfer processes are described quantitatively with a model based on the rate equations [29] and Bloch-Torrey equations [5]. We found that the electron spins generated in the GaAs barrier were transferred coherently into the InGaAs QW within 21 ps.…”
Section: Introductionmentioning
confidence: 97%
“…After this they can be captured into the wetting layer and then recombine with holes or they can recombine directly from the conduction band. This process is described by the following rate equations (10) where the time constants are taken from experimental data of Liu et al (Liu, 2001) ( ps, ps, ns, ns) and the injection rate is chosen to give the desired number of injected electrons. Auger relaxation rate calculations for electrons in a self-assembled dot were first performed by Uskov et al (Uskov, 1997).…”
Section: Auger Relaxation Auger Processes and The Dipole Approximationmentioning
confidence: 99%